Evaluation of the effect of nanofluid-based absorbers on direct solar collector - Saidur, Rahman; Meng, T.C.; Said, Z.; Hasanuzzaman, M.; Kamyar, A. (Elsevier, 2012)
As conventional energy sources like fossil fuels are getting rare, cost of energy production has become higher as well as the concern of environmental pollution by burning of fossil fuels among the developed and developing nations. Solar energy is the most vastly available energy and very effective in terms of energy conversion. The most common solar thermal collector used is the black surface as radiant absorber but the thermal energy efficiency is low. In this study, the effect of nanofluid has been analyzed by using as working fluid for direct solar collector. The extinction coefficient of water based aluminum nanofluid has been investigated and evaluated by varying nanoparticle size and volume fraction. The particle size has minimal influence on the optical properties of nanofluid. On the other hand, the extinction coefficient is linearly proportionate to volume fraction. The improvement is promising within 1.0 volume fraction and the nanofluid is almost opaque to light wave.